Modalitas dan Etika Berita Video 360 Pada YouTube CNN Indonesia - Clara Ariski Paramitha (Jurnal Riset Komunikasi (JURKOM), 2023)
The implementation of immersive journalism as part of digital journalism is now starting to penetrate YouTube. CNN Indonesia is a media company that uses 360 degree video technology to present news. The use of virtual reality technology raises ethical questions that require consideration by news producers to maintain journalistic standards. This study aims to understand the modality and ethics of immersive journalism implemented in CNN Indonesia's 360 degree video content on YouTube through quantitative content analysis. The concept of modality, ethics of immersive journalism, and the theory of media richness are used as analytical tools to understand modality and immersion presented in CNN Indonesia's 360 video. The results of the study show that CNN Indonesia's 360-degree video content follows the ethics of sensitive content, on the other hand, the modalities used are still limited.